Peripheral artery disease is associated with frailty in chronic hemodialysis patients. (August 2018) - Okuyama, Michihiro; Takeuchi, Hidemi; Uchida, Haruhito A; Kakio, Yuki; Okuyama, Yuka; Umebayashi, Ryoko; Wada, Kentaro; Sugiyama, Hitoshi; Sugimoto, Ken; Rakugi, Hiromi; Kasahara, Shingo; Wada, Jun
Objectives: The clinical condition of frailty is a common problem in the elderly population. However, the relationship between peripheral artery disease and frailty in hemodialysis patients remains unknown. The aim of this study was to identify the relationships between peripheral artery disease and frailty in Japanese chronic hemodialysis patients. Methods: A total of 362 chronic hemodialysis patients who regularly visited six institutions were enrolled. To evaluate frailty, the modified Fried's frailty phenotype adjusted for Japanese were used. Peripheral artery disease was defined as ankle-brachial index <0.9. Results: Of 362 patients, 62 patients (17.1%) were categorized as peripheral artery disease group and 300 patients (82.9%) as Non-peripheral artery disease group. The prevalence of frailty in the peripheral artery disease group was significantly higher than in the Non-peripheral artery disease group (34% vs. 18%, P  = 0.0103). Non-shunt side grip strength was significantly stronger in the Non-peripheral artery disease group (23.6 kg vs. 17.0 kg, P  < 0.0001). Thigh circumferences were also significantly larger in the Non-peripheral artery disease group (41.7 cm vs. 39.7 cm, P  = 0.0054). A multivariate logistic regression analysis demonstrated that the factors independently associated with peripheral artery disease were as follows: frailty (odds ratio = 2.06, 95% confidence interval 1.09–3.89) and myocardial infarction (odds ratio = 3.74, 95% confidence interval 2.05–6.83). Conclusions: It is concluded that peripheral artery disease is closely associated with frailty in hemodialysis patients.